Comprehensive analysis of transcriptomics and metabolomics to understand the flesh quality regulation of crucian carp (Carassius auratus) treated with short term micro-flowing water system. (September 2021) - Du, Hongying; Xiong, Shanbai; Lv, Hao; Zhao, Siming; Manyande, Anne
Graphical abstract: Highlights: Improvement of flesh quality/flavor of crucian carp fish muscle by STMFPS treatment. Purine, pyrimidine and glycerophospholipid metabolism were regulated under STMFPS treatment. STMFPS treatment affected the ornithine cycle metabolic pathways in freshwater fish. Abstract: The short term micro-flowing purification system (STMFPS) has been shown to improve the flesh quality of freshwater fish. However, few studies have focused on the involved underlying mechanisms. This study explored the effect of STMFPS on the flesh quality of market-size freshwater fish based on the combination of metabolomics and transcriptomics methods. The UPLC-QTOF/MS based metabolomics method was utilized to screen metabolites and predict the possible major metabolic pathways during different STMFPS treatment periods (0 d, 1 d, 5 d and 9 d). Furthermore, the transcriptomic data demonstrated that the differentially expressed genes detected in crucian carp muscle were 2915, 7852 and 7183 after 1 d, 5 d and 9 d STMFPS treatment. Results showed that the TCA cycle, ornithine cycle, purine metabolism and amino acid catabolism play important roles in improving the flesh quality of crucian carp. This study may help to understand the mechanism of improving the flesh quality of aquatic products using STMFPS.